Chinese EFL Learners’ Lived Experience of Communication Apprehension in a Sino-Foreign Context - Arnel E. Genzola (CV. Literasi Indonesia, 2022)
A great deal of emphasis has been placed on the development of communication competencies among students in light of the significance of effective communication in the 21st century. Past studies identified communication apprehension (CA) as one factor that hindered learners’ ability to communicate effectively. This study used a qualitative, phenomenological method involving six (6) participants who have lived experience of CA in a unique Chinese context, the Sino-Foreign Joint Venture, a concept that promotes cooperation of foreign educational institutions with China’s educational services industry. In-depth interviews, essays of the participants’ experiences, stimulated recall, and classroom observation has been employed. The video-recorded interviews were carried out as the primary method of data collection. The results revealed eight themes identified as anxiety-provoking classroom situations, namely, level of difficulty and familiarity with the topic, incomprehensible input, preparation, interpersonal evaluation and criticism, voluntary speaking and being asked to, making mistakes and losing face, classroom oral presentations, and oral language assessment and rate of recurrence. This study throws in user input to sensitize Sino-Foreign higher education institutions, curriculum developers, and teachers to the debilitating influence of communication apprehension on language learners.